1992
DOI: 10.1177/106002809202600913
|View full text |Cite
|
Sign up to set email alerts
|

The Triglyceride Connection in Atherosclerosis

Abstract: Hypertriglyceridemia is a theoretical risk factor for CHD because of the increased production of atherogenic chylomicron and VLDL remnants, the inverse relationship present between serum triglyceride and HDL, the possible resultant increase in LDL attributable to remnant-reduced hepatic LDL-receptors as well as the formation of more dense and, therefore, more atherogenic LDL, and to the interaction between serum triglyceride and the fibrinolytic/coagulation system. However, most clinical trials that have found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Particularly atherogenic forms of LDL include small, dense LDL particles and oxidized LDL (9). An elevation of VLDL is also associated with increases in prothrombotic and procoagulant factors (11). All lipoproteins that contain apolipoprotein B tend to promote atherosclerosis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly atherogenic forms of LDL include small, dense LDL particles and oxidized LDL (9). An elevation of VLDL is also associated with increases in prothrombotic and procoagulant factors (11). All lipoproteins that contain apolipoprotein B tend to promote atherosclerosis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The data gave us a clue that H 2 might regulate the metabolism of LDL-C by decreasing the synthesis of apoB or increasing the catabolism of LDL-C . Second, like LDL-C, VLDL-C is considered a type of ''bad'' cholesterol because elevated levels are associated with an increased risk of coronary artery disease ( 27 ). We found that apoB and apoE, the major proteins in VLDL, were lowered by H 2 , although cholesterol analysis by FPLC revealed no changes of was not altered signifi cantly after intake of H 2 water (data not shown), which might be attributable to the sensitivity of Griess method.…”
Section: Discussionmentioning
confidence: 99%
“…There is little information concerning this issue so far in the literature. An in-depth study on this point may help in understanding the pathophysiology of hyperlipidemia-induced atherosclerosis, since accumulating evidence from human studies has shown that hyperlipidemia is a major cause of atherosclerosis and cardiovascular disease (CVD) (5)(6)(7), that different types of leukocytes are likely to play important but different roles in atherosclerosis (8)(9)(10), and that a higher peripheral total leukocyte count is associated with an increased incidence of CVD (3,(11)(12)(13). In addition, because cigarette smoking and obesity are frequently found in association with both lipid disorders (14-16) and a higher peripheral leukocyte count (1,3,13,(17)(18)(19), we included the factors of smoking and body mass index (BMI) in the study.…”
mentioning
confidence: 99%